Examining the impact of income diversification on bank performance: Are foreign banks heterogeneous? - Bismark Addai; Wenjin Tang; Annette Serwaa Agyeman (Journal of Applied Economics, 2022)
This study examines the heterogeneity of foreign banks in the income diversification and performance nexus. We utilize annual bank data across 46 countries in Sub-Saharan Africa over the period 2011-2018 and find that increased income diversification improves banks performance, and the Global and Emerging banks perform better than the regional African and domestic banks. Regarding how different foreign banks benefit from income diversification, we find that Global banks benefit from diversification more than their counterparts operating in the region. The Emerging country banks outperform the African and domestic banks, while the local banks in the region benefit from income diversification more than the regional African banks. The results of this study suggest that the emerging banks and the regional African banks do not always exhibit similar features like the Global banks. The observations in this study make significant contribution to the literature by providing new insight into the non-homogeneity of foreign banks in the income diversification pendulum.
Keywords: 330; Bank performance; Foreign ownership; Generalized Method of Moment (GMM); Income Diversification; International banking; Non-interest income